Фотометрический метод определения количества яиц в кладках американской белой бабочки (Hyphantria cunea Dr.) - Генсицкий, И.П.; Богач, А.В. (Вестник зоологии, 1972)
On the basis of the step-by-step magnetic selector of «И-25/8» or «ШИ-11» type, voltage divider and potentiometric bridge of «Pl» type a device is assembled permitting the calibrating curve of any amplitude to be recorded and graduation mark' of the steps to be changed.